2013
DOI: 10.1186/1471-2393-13-137
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of preferences for home or hospital confinement in Pakistan: evidence from a national survey

Abstract: BackgroundDespite the pregnancy complications related to home births, homes remain yet major place of delivery in Pakistan and 65 percent of totals births take place at home. This work analyses the determinants of place of delivery in Pakistan.MethodsMultivariate Logistic regression is used for analysis. Data are extracted from Pakistan Demographic and Health Survey (2006–07). Based on information on last birth preceding 5 years of survey, we construct dichotomous dependent variable i.e. whether women deliver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 7 publications
10
19
0
Order By: Relevance
“…Factors like cultural and religious beliefs might have been stronger in rural areas among marginalised groups. This finding is consistent with other studies [31,33].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Factors like cultural and religious beliefs might have been stronger in rural areas among marginalised groups. This finding is consistent with other studies [31,33].…”
Section: Discussionsupporting
confidence: 94%
“…We could not find any previous studies comparing factors associated with home delivery disaggregated by ethnicity in Nepal. However, several studies demonstrated statistically significant associations of home delivery with mothers age at birth [31], educational level of the mother [32][33][34], wealth status [31,33], province [33], place of residence [31,33], travel time to nearest health facility [32,34,35], and completion of four ANC visits as per national protocol [31,32,34,36].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study, in line with Javed et al (2013), showed that if women consult with others, and especially about their advice regarding childbirth setting, the likelihood of hospital births will increase. In fact, this shows the social influence of group attachment on personal preferences and individual decisions (Lindstrom and Muñoz-Franco 2006).…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with Javed et al (2013) in Pakistan, mothers of Baluch ethnicity are more likely to deliver at home owing to strong cultural norms. Furthermore, when such cultural norms are accompanied by past positive experiences, the likelihood of homebirth will increase.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation